Awareness among Women about Epidural Analgesia in Riyadh, Saudi Arabia - Sarah W. Alnosaier; Asrar A. Alahmadi; Sarah W. Alnafe; Bandar S. Alshehry (Dr. Sulaiman Al Habib Medical Journal)
Background: Labor is a challenging life experience that many women undergo. This experience may cause physical and/or psychological stress before and during the birth process. Part of the stress a woman may experience relates to the pain endured during labor. Epidural analgesia (EA) is an important technique for relieving labor pain. This study aims to assess the awareness of women in Riyadh, Saudi Arabia, regarding the use of EA during labor and to explore ways to improve this awareness. Objective: To assess the awareness level of women in Riyadh, Saudi Arabia, regarding the use of EA during labor. The aim of the research is to contribute valuable insights to maternal care practices and enhance informed decision-making among expectant mothers. Methodology: This cross-sectional study was performed using a validated questionnaire to determine awareness of EA among women in Riyadh, Kingdom of Saudi Arabia (KSA). Participants were randomly selected, and verbal consent was obtained. The sample size was 392. The participants included women of childbearing age, defined by the World Health Organization (WHO) as between 15 and 49 years. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), version 25. The Chi-square test was used to determine the association between demographic characteristics and general knowledge of EA, as well as the association between demographic characteristics and the desire to receive EA. P values were considered significant if ≤0.05. Results: The research sample consisted of 392 women. The majority of participants were between 21 and 40 years of age. A total of 29.1% of participants demonstrated a complete lack of knowledge about EA, while 30.8% reported awareness of EA from multiple sources. The study showed that current marital status, pregnancy status, and previous childbirth experience were not significantly associated with participants’ knowledge of EA. In contrast, age, level of education, current employment status, income, and previous use of EA for vaginal delivery were significantly associated with their knowledge of EA. Interestingly women with no previous experiences of EA for vaginal delivery demonstrated a higher level of knowledge than those who had previously undergone the procedure (59.5% vs. 39.7%). A total of 61.5% of participants expressed a desire to receive EA in the future. The study showed that, while pregnancy status was not significantly associated with the desire to receive EA, all other variables were significantly associated. Among women who preferred that EA be discussed during antenatal visits, the majority favored having the discussion during a consultation with a doctor. Conclusion: The study revealed a significant knowledge gap regarding EA among women in Riyadh, KSA, highlighting the need for comprehensive educational interventions to address this lack of awareness. A large percentage of participants expressed a desire to learn more about EA during routine antenatal visits. This receptiveness presents a valuable opportunity to integrate focused educational initiatives into routine maternal care, empowering expectant mothers to make informed decisions about pain management during labor.